Wittgenstein the way out of the fly-bottle - Schroeder, Severin 1964- (Polity, 2006)
This text offers an account of Wittgenstein's philosophy. Together with a biographical narrative, it explains the key ideas of his work, from his books, the 'Tractatus Logico-Philosophicus', to his masterpiece, the 'Philosophical Investigations'.
Includes bibliographical references (p. [257]-264) and index
Keywords: Wittgenstein, Ludwig -- 1889-1951; Philosophers -- Austria -- Biography; Philosophers -- Great Britain -- Biography; Großbritannien; Österreich; Biografie